Analysis of The Capital Market Reaction To The Anouncement of The Stock Split - Rizky Lubis; Miranda Sondang Olivia Simanjuntak; Keumala Hayati; Nur Aliah (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to determine the effect of stock split announcements on abnormal returns, stock prices, and stock trading volume of companies that carry out stock splits on the Indonesia Stock Exchange for the 2018-2022 period. The sample in this study were companies listed on the IDX that carried out stock splits, totaling 33 companies for five years. This study uses a different test analysis of two paired samples (Paired Sample t-test) with an observation period (event study) of 5 days, namely t = -5 (5 days before the announcement of the stock split), t = +5 (5 days after the announcement stock split). From the research results it can be seen that there is a significant effect of stock split announcements on abnormal returns, stock prices, and stock trading volume, both before and after the announcement